IMPLEMENTATION OF CLASSROOM VISITS THROUGH COLLABORATIVE TEACHING AMONG ECONOMICS EDUCATION STUDENTS - Marsel Nande; Maria Feridiana Uni; Maria Angela Ndarha; Kamilus Nanga; Kristianus Bhae; Afrisinana Manggung (LPPM Universitas Flores, 2026)
This article describes the implementation of classroom visits through teaching collaboration by 4th-semester Economic Education students at SMP Negeri 7 Nangpanda. The activity aims to bridge the gap between theoretical knowledge and teaching practice, equipping prospective teachers with pedagogical, professional, social, and personal competencies. An experiential learning approach was adopted, involving 22 students guided by a supervising lecturer. The implementation consisted of four structured stages: classroom observation, students examined teaching lesson plans (RPP) in accordance with the school curriculum, which were then reviewed by the supervising teacher. During teaching practice, students delivered lessons using interactive lectures, question-and-answer sessions, and group discussions with simple instructional media. In identifying challenges such as nervousness, classroom management difficulties, and limited media variety. Overall, the activity ran well and significantly contributed to improving students' teaching competencies. Students demonstrated responsibility, confidence, and commitment as prospective educators. This activity is recommended as an innovative learning strategy for preparing competent, adaptive, and professionally committed teachers.